Renewing curricula of teacher training: a challenge in the context of the Chilean education reform - Figueroa Sandoval, Beatriz (2016)
The curriculum framework and the necessary elements for teacher training and its implications for the development of skills and attitudes in a training institution Chilena described. A curriculum model adapted to a population with requirements consistent with the social context in which these teachers will perform arises.